Influence of the model view controller (MVC) pattern on the security, interoperability and usability of a computer-system’s life cycle. - Enríquez, Franklin; Fierro , Santiago; Flores, Brandon; Imbaquingo Esparza, Daisy; Michelena , Jaime (EASI: Engineering and Applied Sciences in Industry, 2023)
Applying a design pattern during software development is a common strategy among programmers. In the broad classification of design patterns created to date, there are architectural patterns, one of the most widely used being the Model-View-Controller pattern, also known as MVC. The wide adoption of this pattern has made it necessary to evaluate its impact on security, interoperability and usability throughout the life cycle of a computer system. Through a literature review and research on specialized software development websites, this study reveals that the MVC pattern has a positive influence on these aspects. Furthermore, it was found that the use of this architectural design pattern is considered indispensable and widely popular by the community of experienced developers.
Keywords: Architecture; Design; Pattern; Security; Interoperability; Usability